2015
DOI: 10.1109/tps.2014.2381854
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cold Atmospheric Pressure Plasma Jet Device Driven by Nanosecond Voltage Pulses

Abstract: The structure, fluid-dynamic behavior, temperature, and radiation emission of a cold atmospheric pressure plasma jet driven by high-voltage pulses with rise time and duration of a few nanoseconds have been investigated. Intensified charge-coupled device (iCCD) imaging revealed that the discharge starts when voltage values of 5-10 kV are reached on the rising front of the applied voltage pulse; the discharge then propagates downstream the source outlet with a velocity around 10 7 -10 8 cm/s. Light emission was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 65 publications
5
39
0
Order By: Relevance
“…The plasma source adopted in this work is a single electrode plasma jet, suitable for the treatment of different substrates such as metals, polymers, glasses, and biological materials (Figure ), developed in our laboratory and previously reported in Refs …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma source adopted in this work is a single electrode plasma jet, suitable for the treatment of different substrates such as metals, polymers, glasses, and biological materials (Figure ), developed in our laboratory and previously reported in Refs …”
Section: Methodsmentioning
confidence: 99%
“…In the present work, results regarding the AA plasma polymerization process carried out on a polymeric substrate by using a non‐equilibrium atmospheric pressure nanopulsed plasma jet, are presented.…”
Section: Introductionmentioning
confidence: 99%
“…The lower mole fraction of air can lead to higher local electron concentration. This explains the higher emission intensity from excited species [28,29]. Some authors showed that the increase of gas flow rate is very significant to increase the amount of reactive oxygen and nitrogen species (RONS), which in turn contribute to cell death by damage of the DNA molecules [30].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of nitrogen in the XPS survey spectrum can be probably appointed to the interaction of AA, or the products of its plasma-polymerization, with vibrationally excited N 2 molecules, resulting from the mixing of the plasma plume with the surrounding air, [43] as proposed by Bhatt et al [54] for the case of plasmapolymerization of diethylene glycol dimethyl ether; indeed, they observed by means of optical emission spectroscopy the formation of OH, CH, N 2 , and CN excited species when the monomer was introduced into the Ar plasma jet. The curve fitting of the high-resolution C 1s peak, shown in Figure 7, provides useful information on the retention of carboxyl groups in the chemical structure of the pPAA matrix of the nanocomposite coating.…”
Section: Resultsmentioning
confidence: 99%